Eosinophilic dermatosis of hematologic malignancy in patients with chronic lymphocytic leukemia/non-Hodgkin’s B lymphoma: a single center prospective clinico-pathological study - Michelerio, Andrea; Tomasini, Carlo; Fiandrino, Giacomo; De Amici, Mara; Varettoni, Marzia; Defrancesco, Irene; Cavalloni, Chiara; Brazzelli, Valeria; Derlino, Federica; Paulli, Marco; Arcaini, Luca; Vassallo, Camilla (Frontiers in Medicine, 2023)
Background: The pathogenesis of eosinophilic dermatosis of hematological malignancy (EDHM) is poorly understood. Previously thought to be a hypersensitivity reaction to insect bites, immune dysregulation and cytokine imbalance are now thought to be responsible. Its prognostic significance is unclear. Objective: To describe the clinical, pathological and immunological findings in a series of oncohematological patients with EDHM. Methods: an observational prospective cohort study of oncohematological patients receiving a diagnosis of EDHM between April 2017 and December 2018. Results: A total of 15 patients with EDHM (10 females and 5 males) were identified among 422 oncohematological patients. Disease presentation varied from firm erythematous papules to more polymorphic presentations. The lesions were most prevalent on the exposed sites, 8/15 patients recalled an insect bite. Lesion seasonality was reported in 13/15 patients. IgE levels were elevated in six patients, circulating IL-4 and IL-5 were within a normal range. Twelve out of 15 patients developed skin manifestations after chemotherapy. The infiltrate could be eosinophil-rich or lymphocytic-rich. Interestingly, the histopathologic findings were in accordance with arthropod bites. Conclusion: A role for insect bites in EDHM is supported by our findings. EDHM may be related to aggressive hematologic disease